2012
DOI: 10.1111/j.1365-2214.2012.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in newly diagnosed children with specific learning disabilities (SpLD) and differences from typically developing children: a study of child and parent reports

Abstract: The results may suggest certain significant effects of the SpLD condition on newly diagnosed children's QoL. Emotional and social deficits seem to be experienced by this cohort of children and their parents. Investigation into the possible interrelationships between parental and child QoL seems to indicate that parental social wellbeing may to a certain extend influence some dimensions of the child's QoL. The findings are useful for policy making and specialized interventions for children with SpLD and their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
6
36
0
1
Order By: Relevance
“…Our results are partly similar to the findings of Ginieri-Coccossis et al (2013); according to self-report, no differences were found between RD and control groups for both genders in the QoL dimensions of physical well-being and school functioning. Moreover, the very few previous studies measuring the self-rated QoL of children with SpLD reported lower self-rated QoL of children with SpLD than typically developing children in the dimensions of emotional well-being and family and friends (Karande et al, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012; Ginieri-Coccossis et al, 2013). However, in our study, children (both girls and boys) did not rated their QoL lower on the dimension of family and general QoL than did healthy children.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are partly similar to the findings of Ginieri-Coccossis et al (2013); according to self-report, no differences were found between RD and control groups for both genders in the QoL dimensions of physical well-being and school functioning. Moreover, the very few previous studies measuring the self-rated QoL of children with SpLD reported lower self-rated QoL of children with SpLD than typically developing children in the dimensions of emotional well-being and family and friends (Karande et al, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012; Ginieri-Coccossis et al, 2013). However, in our study, children (both girls and boys) did not rated their QoL lower on the dimension of family and general QoL than did healthy children.…”
Section: Discussionsupporting
confidence: 92%
“…Our study extends several aspects of the existing, but very limited data on the QoL of children with an RD (Karande et al, 2009; Karande and Bhosrekar, 2009; Rotsika et al, 2011; Karande and Venkataraman, 2012, 2013; Ginieri-Coccossis et al, 2013). …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The presence of literacy problems and weak GPA may have several unfortunate consequences, such as depression, anxiety, loneliness and poorer quality of life (Ginieri-Coccossis et al, 2013;Klassen et al, 2013), more frequent risk behaviour, substance use, aggressive and delinquent acts (McNamara & Willoughby, 2010), as well as drop-out from school (Goldstein et al, 2011). Yet, more adolescents with literacy problems attend higher education than before.…”
Section: Cognitive/school-related Factorsmentioning
confidence: 99%